Nanoengineered Surfaces for Thermal Energy Conversion. (November 2015) - Bhatia, Bikram; Preston, Daniel J; Bierman, David M; Miljkovic, Nenad; Lenert, Andrej; Enright, Ryan; Nam, Youngsuk; Lopez, Ken; Dou, Nicholas; Sack, Jean; Chan, Walker R; Celanović, Ivan; et al.
Abstract: We provide an overview of the impact of using nanostructured surfaces to improve the performance of solar thermophotovoltaic (STPV) energy conversion and condensation systems. We demonstrated STPV system efficiencies of up to 3.2%, compared to ≤1% reported in the literature, made possible by nanophotonic engineering of the absorber and emitter. For condensation systems, we showed enhanced performance by using scalable superhydrophobic nanostructures via jumping-droplet condensation. Furthermore, we observed that these jumping droplets carry a residual charge which causes the droplets to repel each other mid-flight. Based on this finding of droplet residual charge, we demonstrated electric-field-enhanced condensation and jumping-droplet electrostatic energy harvesting.